PENINGKATAN KETERAMPILAN DIGITAL SISWA SMP ISLAM BAHRUL ULUM MELALUI PELATIHAN WEBSITE BUILDER - Septa; Syndhe Qumaruw Syty; Diki Rasapta (Abdi Jurnal Publikasi, 2025)
The digital era presents a paradox where the younger generation, despite being adept technology users, often lacks productive digital skills. This gap limits their potential to transition from passive content consumers to active creators. This community service program was designed to address this challenge by enhancing the digital literacy and technical skills of students at SMP Islam Bahrul Ulum through website creation training. The program utilized a workshop method with a Project-Based Learning (PBL) approach, engaging 30 seventh-grade students. To ensure accessibility, the training employed a no-code website builder platform, removing the technical barriers associated with programming. The program's effectiveness was measured using pre-test and post-test evaluations, which demonstrated a significant increase in conceptual understanding, with the average score rising from 42 to 86. Furthermore, practical skill acquisition was evidenced by 93% of participants successfully creating and publishing a functional website. The findings confirm that this structured intervention effectively transformed students into confident digital creators, equipping them with foundational skills for the digital economy. This initiative serves as a replicable model for bridging the digital skills gap in similar educational contexts.